Fall of the School for Good and Evil - Chainani, Soman (Chainani, Soman. School for Good and Evil, 2023)
Two brothers who rule the School for Good and Evil in exchange for power and immortality find their loyalty corrupted, bringing them to the brink of war and a shocking conclusion that will change the course of the school forever.